Severe fetal ventriculomegaly: Fetal morbidity and mortality, caesarean delivery rates and obstetrical challenges in a large prospective cohort. (6th December 2021) - Start, Alex O.; Ryan, Gillian A.; Cathcart, Barbara; Hughes, Heather; Higgins, Shane; Corcoran, Siobhan; Walsh, Jennifer; Carroll, Stephen; Mahony, Rhona; Crimmins, Darach; Caird, John; Colleran, Gabrielle; et al.
Abstract: Introduction: Severe fetal ventriculomegaly (VM) is defined as an enlargement of the atria of the lateral cerebral ventricles (Vp) of greater than 15 mm. While it is well established that it confers significant risk of morbidity and mortality to the neonate, there is limited information pertaining to the caesarean delivery rates and the obstetric management of these complex cases. The aim of this study was twofold: firstly, to determine survival rates in fetuses with severe VM, and secondly to determine the caesarean delivery rates in continuing pregnancies. We explore the obstetric challenges associated with these difficult cases. Methods: This was a prospective observational study of patients with antenatal severe VM, attending the Department of Fetal Medicine, National Maternity Hospital, Dublin, Ireland, from 1st January 2011 to 31st July 2020. Data were obtained from the hospital database and those with severe VM (Vp > 15 mm) were identified. The rates of chromosomal abnormalities, the survival rates and the caesarean delivery (CD) rates for the overall group were then determined. The data were then further sub‐divided into two groups: 1. Vp < 20 mm and 2. Vp > 20 mm, and the results compared. Statistical analysis was performed using the Chi‐Square test. Results: A total of N = 95 pregnancies with severe VM were included for analysis, of which additional structural abnormalities on ultrasound were apparent in 67/95 (70.5%) and 28/95 (29.5%) had isolated severe VM. Chromosomal abnormalities were diagnosed in 15/95 (15.8%) of cases, with (2/28) 7.1% in the isolated SVM group versus (13/67) 19.4% in the non‐isolated SVM group. The overall survival rate (excluding TOP) was 53/74 (71.6%), with 20/23 (86.9%) in the isolated SVM group. The overall CD rate was 47/72 (65.3%), which was significantly higher than the CD for the hospital during the same time period of 25.4% ( P < 0.01). The data were subdivided into Vp < 20 and Vp > 20 and those with a Vp > 20 had higher rates of additional intracranial findings on ultrasound (Vp < 20 13/41 (31.7%) versus Vp > 20 32/54 (59.3%) ( P < 0.05)) and macrocrania (Vp < 20 14/41 (34.1%) versus Vp > 20 35/54 (64.8%) ( P < 0.05)). No significant difference was observed in the overall survival or CD rates between the two groups. Conclusion: In conclusion this study reports significant fetal morbidity and mortality with severe VM with high CD rates observed in this cohort. Significant challenges exist in relation to the obstetric management and counseling of parents regarding an often uncertain neonatal prognosis. In continuing pregnancies with significant macrocrania delivery plans should be individualized to improve neonatal outcomes where possible and minimize harm to the mother. Key points: What's already known about this topic? Severe ventriculomegaly is associated with fetal morbidity and mortality There is paucity of data on the outcomes of Vp > 20 mm versus Vp < 20 mm There is limited information about caesarean delivery rates of these cases What does this study add? The overall survival (excluding TOP) was 71% No differences were observed in overall survival or CD rates between Vp > 20 mm versus Vp < 20 mm The overall caesarean delivery rates were 65% in this cohort